2017
DOI: 10.21276/ijirem.2017.4.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Gas Turbine Power Plant

Abstract: Gas Turbine power plants are being used for producing electricity, operating airplanes and for various industrial applications such as refineries and petrochemical plants. In this paper, thermodynamic performance analysis of an open cycle gas turbine power plant has been performed. The mathematical formulation for the specific work and efficiency were derived and analyzed. The effect of operating parameters like the ambient temperature, relative humidity, compressor pressure ratio, turbine inlet temperature (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…(Exhaust) to the atmosphere at a temperature of about 600 °C at point (4) and with the rotation of the turbine shaft, the shaft of the electric generator of the unit rotates to produce energy At the same time, the main air compressor shaft is self-rotating with mechanical energy [12]. Figure (1) represents the diagram of the Brayton cycle and Gas turbine components.…”
Section: Materials and Methods Power Plant Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Exhaust) to the atmosphere at a temperature of about 600 °C at point (4) and with the rotation of the turbine shaft, the shaft of the electric generator of the unit rotates to produce energy At the same time, the main air compressor shaft is self-rotating with mechanical energy [12]. Figure (1) represents the diagram of the Brayton cycle and Gas turbine components.…”
Section: Materials and Methods Power Plant Componentsmentioning
confidence: 99%
“…Electric energy is the vital artery for running the daily business of societies in our time. The demand for electricity all over the world is constantly increasing, and the rate of this increase reaches 8% in developed countries and 25% in developing countries [1]. Recent years have been characterized by a high rate of use of bare stations to produce the electrical energy required to cover the load of the electrical network in Iraq, due to the small size of these units relative to the energy produced, which leads to their need for a short time for construction compared to steam units.…”
Section: Introductionmentioning
confidence: 99%
“…The gas turbine parameters are the ones that influence the performance of CCGT significantly [4]. The major influencing gas turbine parameters are compressor pressure ratio, air-fuel ratio, turbine inlet temperature, and isentropic efficiencies of compressor and gas turbine [5,6]. The performance speculation of any energy system is carried out by thermodynamics means.…”
Section: Introductionmentioning
confidence: 99%
“…Few researchers have studied the effect of the aforementioned gas turbine parameters on this exergy-based performance factor. Ankit et al [6] studied the effect of compressor pressure ratio and isentropic efficiency on the thermal efficiency of the gas turbine cycle. It was observed that increasing the pressure ratio and isentropic efficiency increases the thermal efficiency as per a higher value of the air-fuel ratio.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that rising human electric energy consumption has a direct impact on economic growth. More energy is stimulated by this economic growth [1].…”
Section: Introductionmentioning
confidence: 99%